Dealing With the Pandemic of COVID-19 in Portugal: On the Important Role of Positivity, Experiential Avoidance, and Coping Strategies - Ferreira, Maria José; Sofia, Rui; Carreno, David F.; Eisenbeck, Nikolett; Jongenelen, Inês; Cruz, José Fernando A. (Frontiers in Psychology, 2021)
The global COVID-19 pandemic crisis has caused an unprecedented impact on most areas of people’s lives. Thus, framed within the scope of Existential Positive Psychology (PP2.0), this study aimed at assessing the psychological distress of adults living in Portugal during the first national lockdown, how they are coping with stress, as well to contribute to a deeper understanding about the role that positivity, experiential avoidance, and coping strategies have in psychological distress and well-being. For this purpose, 586 Portuguese adults (73% females) ranging between 18 and 78 years old (M = 38.96, SD = 12.20) completed an online survey during the initial phase of the pandemic crisis in Portugal. Findings suggest that experiential avoidance was the strongest predictor of a negative response (depression, anxiety, stress, loneliness, and negative emotions), whereas positivity was a better predictor of psychological well-being and lower levels of depression. Additionally, self-blame, behavioral disengagement, and emotional venting were strong risk factors for psychological distress, whereas positive reframing, planning, and acceptance were associated with more positive outcomes. These findings highlight the critical role of experiential avoidance on individuals’ psychological distress and the essential contribution of positive life orientation in promoting flourishing. By offering a better understanding of the complex navigation through the dialectics between positive and negative life features, this study provides important and useful cues for psychological interventions directed at promoting a more positive and adaptive human functioning even through such potential adverse and painful life events.